Analisis Kontribusi PT Intidaya Agrolestari (Inagro) terhadap Lapangan Pekerjaan Penduduk Sekitar sebagai Mekanisme Pertumbuhan Ekonomi dalam Pencapaian Sustainable Development Goals - Lawita, Florencia Irena; Kurniawan, Budi; Christian, Matthew; Permatasari, Intan (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze the contribution of PT Intidaya Agrowisata (INAGRO) to employment opportunities for residents around PT Intidaya Agroconservali as a mechanism for economic growth in Bogor Regency in achieving the Sustainable Development Goals. This research was conducted by interviewing six workers at INAGRO. The data used includes previous research, current data from relevant sources, books, and various reports related to the topic studied. The interpretive-phenomenological method is the data analysis used in this research. The results of the research state that PT Intidaya Agrowisata (INAGRO) contributes effectively to creating employment opportunities for the villagers around INAGRO which can be useful as a mechanism for economic growth in achieving the Sustainable Development Goals. INAGRO provides productive work opportunities for village communities. Every village from the 4 sub-districts around INAGRO, is invited to work at INAGRO in accordance with INAGRO's needs, INAGRO can contribute as a mechanism for economic growth in achieving the Sustainable Development Goals (Goal 8), that INAGRO with its context as a tourist spot and place of work for residents is supported by opportunities very productive work.